Carboniferous–Permian tectonic framework and its later modifications to the area from eastern Kazakhstan to southern Altai: Insights from the Zaysan–Jimunai Basin evolution. (1st December 2015) - Li, Di; He, Dengfa; Ma, Delong; Tang, Yong; Kong, Yuhua; Tang, Jieyun
Graphical abstract: Highlights: The ca. 313 Ma basalts from Well JC1 are defined in the Zaysan–Jimunai Basin. The Upper Carboniferous series formed in an island arc setting. Double subduction of Irtysh–Zaysan Ocean persisted until the Late Carboniferous. The area from eastern Kazakhstan to southern Altai experienced episodic modifications since Permian. Abstract: The Zaysan–Jimunai Basin is located in the area from eastern Kazakhstan to southern Altai. The structural deformation and sedimentary filling succession of this basin are a response to amalgamation processes and the intracontinental evolution of the Zharma–Saur and Altai terranes. This paper focuses on the Carboniferous–Early Permian tectonostratigraphic evolution and the Mesozoic–Cenozoic structural patterns of the Zaysan–Jimunai Basin using 2D and 3D seismic reflection profiles and geochronological and geochemical data to reveal an integrated Carboniferous–Permian tectonic framework and its later modifications to the area from eastern Kazakhstan to southern Altai. The Jimunai Basin comprises Devonian–Lower Carboniferous, Upper Carboniferous, Lower Permian and Paleogene strata, while the Zaysan Basin preserves the Mesozoic, Carboniferous–Permian and Cenozoic strata. The possible Devonian–Lower Carboniferous strata exhibit oppositely oriented thrust imbricate structures. The Late Carboniferous–Lower Permian strata are characterized by a fan-shaped filling pattern. The Mesozoic and Paleogene strata are dominated by high-angle thrust faults across/along the tectonic belt. The Late Carboniferous strata from Well JC1 in the Jimunai Basin are composed of dark grey basalt, andesite, tuff and minor pyroclastic rocks. The basalt was dated using zircon SIMS U–Pb method, yielding an age of 313.2 ± 2.1 Ma. These basalts belong to the calc-alkaline series and are characterized by low TiO2 and Th contents, low initial 87 Sr/ 86 Sr, high whole rock ε Nd ( t ) and zircon ε Hf ( t ) values, enrichment in LREEs and depletion of Nb and Ta, suggesting that they are most likely derived from partial melting of a spinel Iherzolite and garnet-bearing peridotite mantle metasomatized by subduction-related fluids and slab melts in an island arc setting. The data presented here are combined with previous works to propose a double subduction model for the Irtysh–Zaysan Ocean in the area from eastern Kazakhstan to southern Altai. During the Carboniferous, the Saur terrane underwent tectonic transition from flat subduction (to slab rollback) to normal subduction compared to the continued normal subduction of the Altai area. The angular unconformity between the Upper Carboniferous and Lower Permian series most likely indicates the closure of the Irtysh–Zaysan Ocean. The high-angle thrust and growth strata in the basin suggest that area from eastern Kazakhstan to southern Altai experienced episodic modifications related to transpressional events from the Messozoic to the Paleogene.